Tourist Attraction Development Strategy Of Al Munawar Arab Village, Palembang - Kusumawardhani, Mega Nurintan; Mulyantari, Enny; Susilowati, Heni; Rosilawati, Yeni (JURNAL DESTINASI PARIWISATA; Vol 10 No 1 (2022): VOL 10, NO 1 (2022): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2022.v10.i01.p20, 2022)
This research aims to determine the development strategy of Al Munawar Arab Village as a tourist attraction in Palembang City. Al Munawar Arab Village can be developed because of the diversity of attractions it has, some of which are eight buildings included in the cultural heritage, Arab ethnic culture, and religious activities. However, the managers have not applied a good strategy for developing tourist areas, as seen from the decline in tourist visits from time to time. This study used a mixed-method combining quantitative and qualitative data input at the same time. The resulting quantitative analysis was the value of weighted, rating, and attractiveness scores. In contrast, the qualitative analysis was the external and internal environment, the interpretation of scores on the EFAS, IFAS, and IE matrix, and SWOT. The SWOT analysis utilized three essential elements of tourism products: attractions, amenities, and accessibility. Based on the EFAS matrix, the enormous opportunity in functional attraction development was the availability of floating docks for further development with a weighted score of 0.380. Moreover, the biggest threat was similar tourist areas which were more attractive with a weighted score of 0.140. The IFAS matrix revealed that the greatest strength in the functional development of tensile data was the eight buildings included in the cultural heritage, with a weighted score of 0.260. In comparison, the biggest weakness was the lack of human resources in the development of tourist areas, having a weighted score of 0.053. The total weight score for EFAS and IFAS was 2.710 and 2.840, respectively, which were in the average position. Based on the weighted score, the functional position of developing tourist attractions in Al Munawar Arab Village was in cell V, hold and maintain. The strategies used were market penetration and product development. Keywords: Development Strategy, Tourist Attraction